Old habits die hard: assessing the validity of using homicide as an indicator of other violent crimes - Breen, Jolien van (European journal of criminology, 2024)
Homicide statistics are often used as an indicator for violent crime more generally. In this work, we evaluate the empirical support for this convention in a Western European context, specifically the Netherlands. Using data from Statistics Netherlands (CBS) and from the Dutch Homicide Monitor, we compare homicide rates to rates of other violent crimes between 2010 and 2020. Results show that homicide and violent crimes are related in a general sense, but it is difficult to say what those relationships look like concretely. In other words, there is an empirical relationship between homicide and the overarching concept of violent crime, but relationships between homicide and individual violent crimes vary considerably. Based on these findings, we advise that researchers tread carefully when using homicide as an indicator of violent crime.